Treatment Outcomes of Epithelial Ovarian Cancer A Longitudinal Study - Kerio, Perwasha; Abid, Khadijah; Hassan, Anusha; Shah, Aamera; Manzoor, Ammara (Asian Pacific Journal of Cancer Care, 2022)
Objective: To evaluate the treatment outcomes in patients with epithelial ovarian cancer following neoadjuvant chemotherapy presenting at a tertiary care hospital. Materials and methods: It was a longitudinal study conducted at the department of medical oncology, Jinnah postgraduate medical center, Karachi Pakistan from May 2018-Feb 2020. One twenty-five women of age 20-80 years with confirmed diagnosis of ovarian carcinoma (stage 1-4) who were referred from different medical institutes of Karachi were included in the study. Surgery and systematic chemotherapy were the primary treatment at the time of ovarian cancer diagnosis. Until death or last follow-up, treatment results were measured. Based on the treatments received from recurrence, systematic chemotherapy was further classified as 2nd line and 3rd line. Females who relapse after 6 months with platinum based treatment were underwent for re-treatment with carboplatin and cisplatin in combination or alone or those who recurred within 6 months and progress on 1st line were treated with non-platinum based systematic chemotherapy. SPSS version 23 was used to analyze data. Results: The mean age of the study sample was reported as 46.23 years. The cumulative survival proportion of complete remission after first line platinum based chemotherapy with respect to duration of 1st line therapy was estimated as 0.027 and the median survival time was reported as 135 (95% CI: 128.81-141.18) days. The cumulative survival proportion of complete remission after second line chemotherapy with respect to duration of 2nd line therapy platinum based was estimated as 0.82 and the median survival time was reported as 156 (95% CI: 144.18-167.81) days. Hence, statistically significant difference was observed between platinum and non-platinum based chemotherapy (p=0.008) in second line therapy. Whereas, no case of complete remission occurred after third line chemotherapy. Conclusion: The chemotherapy based on platinum (1st line) showed complete remission in most of the patients. After second line therapy, few patients showed disease progression and they underwent for third line therapy. The median time from 2nd line therapy to 3rd line therapy was reported as 123 days. In third line therapy, majority patients received non-platinum based chemotherapy where majority showed disease progression. The median survival time of 2 patients who died during third line therapy was reported as 8.75 months. The median survival time after 1st line therapy was 150 days. The median survival time after 2nd line therapy was 156 days.